A REVIEW OF GLOBAL NAVIGATION SATELLITE AND AUGMENTATION SYSTEMS - Lawal, Lasisi Salami; Chatwin, Chris Reginald (IJRDO - Journal of Electrical And Electronics Engineering, 2019)
The importance and application of global navigation satellite systems (GNSS) has never been greater; there is increasing demand for both commercial and government projects; indeed, owning and operating a GNSS facility has become a matter of national esteem. This article reviews some of the history that led up to the USA building its benchmark Global Positioning System (GPS) exploiting electromagnetic waves and reviews the progress being made by other nations and regions in constructing accurate navigation positioning systems.